Principles of Methodology: Research Design in Social Science - Burkhardt, Jason T. (Journal of MultiDisciplinary Evaluation, 2012)
A review of the book Principles of Methodology: Research Design in Social Science by Perri 6 and Christine Bellamy, published in 2012 by SAGE.